THE CORRELATION BETWEEN KNOWLEDGE LEVEL WITH ADOLESCENT'S BEHAVIORS ABOUT FREE SEX BASED ON REPRODUCTIVE HEALTH LAW REGULATIONS IN SMA R BANDUNG - Hariningsih, Wintari; Sinaga, Saurmian; Pereira, Silvia Mendes; Kurnianto, Andreas (Universitas Airlangga, 2022)
Introduction: Reproductive Health has been managed by the Indonesian government in regulation and It is said that reproductive health services aim to prepare adolescents for a healthy responsible reproductive life. One of the problems that occur during the adolescence period is free sex. Commonly, it is affected by various elements, like ignorant, relationships with family or parents, and promiscuity. This condition will give an impact on their future if it is not handled properly. This study was intended to find out the correlation between students' understanding level with their behavior of free sex in SMA R. Bandung. Methods: In line with the aims of the study, it was categorized as a quantitative research design using a cross sectional approach. The data collection technique used a questionnaire of comprehension and teenagers' behavior of premarital sex. The research sample consists of 69 students, namely in class X and class XI as the population. However, only 26 students of class X consist of 12 men and 14 women, and 43 students of class XI consist of 19 men and 24 women. Results: From univariate analysis, it can be seen that most respondents (68.1%) had good knowledge. meanwhile. they also showed (81.2%) a positive behavior. This indicates that bivariate analysis obtained a p-value of 0.000 or signified<0.05. Conclusions: In a conclusion, there was a correlation between students' knowledge level and their behavior of free sex in SMA R Bandung.